Emergency treatment of adrenal crisis with prednisone suppositories: a bioequivalence study in female patients with Addison's disease. Issue 4 (April 2019) - Burger-Stritt, Stephanie; Bachmann, Linda; Kurlbaum, Max; Hahner, Stefanie
Abstract : Objective: Patients with adrenal insufficiency (AI) need to adapt their glucocorticoid replacement under stressful conditions to prevent adrenal crisis (AC). Prednisone (PN) suppositories are used for emergency treatment. Pharmacokinetics of 100 mg PN suppositories after vaginal or rectal administration was evaluated. Design: Single-center, open-label, sequence-randomized, cross-over, bioequivalence study. Methods: Twelve females with primary AI were included. Comparison of pharmacokinetics after vaginal and rectal administration of 100 mg PN suppositories. Main outcome measures: bioequivalence (Cmax : maximum plasma concentration of prednisolone; AUC0 –360 : area under the plasma concentration curve of prednisolone from administration to 360 min), adrenocorticotropin (ACTH) levels, safety and tolerability. Comparison of ACTH-suppressive effect with subcutaneous and intramuscular administration of 100 mg hydrocortisone. Results: Vaginal administration of PN suppositories was not bioequivalent to rectal administration: Cmax and AUC0–360 were significantly lower after vaginal compared to rectal administration: 22 ng/mL (109%) vs 161 ng/mL (28%), P < 0.001; 4390 ng/mL * min (116%) vs 40, 302 ng/mL * min (26%), P < 0.001; (mean (coefficient of variation), respectively). A suppression of ACTH by >50% of baseline values was observed 149 min (32%) after rectal PN administration; after vaginal PN administration, the maximum decrease within 360 min was only 44%. Adverse events were more frequent after vaginal administration and mainly attributable to the glucocorticoid deficit due to inadequate vaginal absorption. The ACTH-suppressive effect was more pronounced after parenteral hydrocortisone compared to rectal or vaginal PN. Conclusion: Vaginal administration of PN suppositories in the available form is not useful for prevention of AC. Pharmacokinetics after rectal use of PN show inferiority compared to available data on parenteral glucocorticoids. In adrenal emergencies, hydrocortisone injection should be the first choice.